IMPLEMENTASI PROGRAM IPTEK BAGI MASYARAKAT KELOMPOK PERAJIN LIMBAH PLASTIK DI KELURAHAN KARUNRUNG DAN MAKKIO BAJI KECAMATAN RAPPOCINI KOTA MAKASSAR - Ridwan Ridwan (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
This article describes the results of the Science and Technology for Society (IBM) for training, coaching and mentoring on Craft Group Karunrung Plastic Waste in the village and sub-district Bontomakio Rappocini Makassar. This activity aims to : (1) increase the motivation for entrepreneurship partner members, (2) enhance the ability of members of the technical partners in production and marketing, (4) increase the number and quality of the production of associate members, (4) improving the understanding and participation of associate members of the plan business and good management. Outcomes achieved from this program are : (1) increasing the entrepreneurial spirit and the spirit of partner members in an effort to support group activities, (2) the group has the knowledge and skills partners and pemasaan production, (3) with the increasing productivity partner group, (4) group partners have the ability to make a simple business plan, established institutional partner organizations, (5) increased faculty attention to the group of crafters Nobel STIE plastic waste, and (6) increased activity in the development of science and technology STIE Nobel Indonesian. While the physical outcomes of this program is in the form of object carried in the hand bag, school bag, decoration curtains, different types of flowers (flowervase ), key chains, glass cover, water spots and other minirel.